Laparoscopic cholecystectomy using endoloop ligation in a bitch with biliary disorders - Da Silva, Fernanda Costa; Do Nascimento, Kelly Karoline Gomes [UNESP]; Lima, Francisco Wanderson Bizerra; Frantz, Daiane Michele; de Oliveira Monteiro, Francisco Décio; Teixeira, Pedro Paulo Maia (Editora da Universidade Federal Rural do Semi-Arido - EdUFERSA, 2024)
A 4-year-old female poodle presented with eosinophilia and increased alanine aminotransferase during routine evaluation. Ultrasound examination revealed findings suggestive of mild liver steatosis, biliary mucocele, cholelithiasis, and cholecystitis, and conservative treatment was indicated. Thirty days later, the patient had diarrhea, abdominal pain, and weight loss. Laboratory examination revealed thrombocytopenia, hyperbilirubinemia, and increased activity of alkaline phosphatase and alanine transaminase. Based on the progressive changes in the exams and the condition suggestive of moderate to severe cholecystitis, a laparoscopic cholecystectomy with an endoloop ligature was performed. The dog recovered from surgery and anesthesia without complications and was discharged the next day. Amoxicillin with clavulanate, meloxicam, dipyrone, and tramadol hydrochloride were prescribed as a postoperative drug. The patient’s recovery was quick and uneventful. Laparoscopic cholecystectomy was efficient in the treatment of bile duct disease of this bitch and the use of an endoloop was shown to be efficient for sealing the bile duct in this case.
Colecistectomia laparoscópica com ligadura endoloop em cadela com distúrbios biliares
Keywords: Biliary tract endosurgery; cholecystitis; cystic duct ligation; laparoscopic suturing